Acute Megakaryocytic Leukemia (FAB M7) - Ara, T; Zaman, MK; Afrose, S; Islam, MS; Biswas, AR; Khan, MA; Rahman, MM (Journal of Dhaka Medical College, 2011)
Acute megakaryocytic leukemia (AML M7) is a rare type of acute leukemia often presented with myelofibrosis.This report describes a 65 years old female who presented with progressive weakness and fatigue. She was diagnosed as a case of de novo AMLM-7 on the basis of peripheral blood finding, bone marrow examination report and immunophenotyping. She refused chemotherapy, received only supportive therapy and died after two months of diagnosis. Key Words: Acute megakaryocytic leukemia; thrombocytosis; immunophenotyping. DOI: http://dx.doi.org/10.3329/jdmc.v20i1.8590 J Dhaka Med Coll. 2011; 20(1) :89-92